Media Sosial Whatsapp Sebagai Media Pembelajaran Jarak Jauh Mata Kuliah Ilmu Sosial Budaya Dasar (ISBD) - Muhammad Awin Alaby (Jayapangus Press, 2020)
Whatsapp as one of the most popular social media and widely used by people in Indonesia. In Indonesia on the Covid 19 pandemic today many students are already using gadgets in their daily activities both on campus and off campus. Most of these students use social media applications, especially Whatsapp which is easy to use as a distance learning media. This study aims to determine the role of Whatsapp social media in Distance Learning in addition to communicating and delivering messages in lecture material. WhatsApp also provides information services related to lecture learning programs that are connected in a Whatsapp group between Lecturers and Students. This paper also aims to see how to use WhatsApp as a Distance learning media. The research method used is descriptive qualitative, interactive data analysis techniques through observation and interviews. Based on the results of the study it can be concluded that whatsapp social media as a learning media is very instrumental in the lecture process that serves as a means of education, an evaluation tool, a means of connecting information, and a means of consulting services.